Film and Video Needs: One State's Assessment - Kathleen A. DeMarco (Journal of Applied Communications, 1984)
Cooperative Extension agents and subject matter specialists at land-grant universities throughout the United States use every bit of educational media at their disposal, especially electronic media, to reach their clientele.